Religious Environmental Activism Emerging Conflicts and Tensions in Earth Stewardship - Koehrsen, Jens; Blanc, Julia; Huber, Fabian (Routledge Studies in Religion and Environment, 2023)
This volume explores how religious and spiritual actors engage for environmental protection and fight against climate change. Climate change and sustainability are increasingly prominent topics among religious and spiritual groups. Different faith traditions have developed ""green"" theologies, launched environmental protection projects and issued public statements on climate change. Against this background, academic scholarship has raised optimistic claims about the strong potentials of religions to address environmental challenges. Taking a critical stance with regard to these claims, the chapters in this volume show that religious environmentalism is an embattled terrain. Tensions are an inherent part of religious environmentalism. These do not necessarily manifest themselves in open clashes between different parties but in different actions, views, theologies, ambivalences, misunderstandings, and sometimes mistrust. Keeping below the surface, these tensions can create effective barriers for religious environmentalism. The chapters examine how tensions are manifested and dealt with through a range of empirical case studies in various world regions. Covering different religious and spiritual traditions, they reflect on intradenominational, interdenominational, interreligious, and religious-societal tensions. Thereby, this volume sheds new light on the problems that religions face when they seek to take an active role in today's societal challenges. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license.